Implementing the Project-Based Learning Model to Improve Junior High School Students' Communication Skills: Systematic Review - Nurhamudin; Sugiharto, Bowo; Karyanto, Puguh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to determine the impact of implementing the Project-Based Learning (PjBL) learning model on improving students' communication skills. This study used a Systematic Literature Review (SLR). Systematic Literature Review involves searching and analysing relevant literature from various sources published from 2016 to 2024. A systematic method is used to identify literature studies that meet the criteria. The criteria for the literature to be analysed have been previously determined. Content analysis is used to ensure the model, method, focus, and results achieved from the study. The results of this literature review reveal that (a) Project-Based Learning improves students' communication skills in which 85% of studies indicate that PjBL consistently improves students' communication skills, especially in the aspects of speaking, listening, and collaborating, (b) Project-Based learning is suitable to use in teaching and learning activities in which ollaborative activities in PjBL, such as discussions, presentations, and reflections, allow students to interact, convey ideas, and receive feedback actively, and (c) Project-based learning is effective in science learning, especially to improve communication skills. Educators should consider using the project-based learning model in learning strategies to support students' communication skills development comprehensively.